Paradigma Fatwa Pemboikotan Produk Pro-Israel: Implikasi terhadap Pekerja Muslim di Kota Makassar: Implications for Muslim Workers in Makassar City - Rizka, Husnul; Anwar, Muhammad Said (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aimed to analyze the implications of the Indonesian Ulama Council (IUC) Fatwa Number 83 of 2023, which recommended a boycott of products affiliated with Israel as a form of religious solidarity with the struggle of the Palestinian people. The main focus of this study was to examine the social, economic, and professional impacts of the fatwa on Muslim workers working in companies affiliated with Israeli products in Makassar City. This study used a phenomenological approach within a qualitative research framework, with data collection through in-depth interviews and participant observation, as well as thematic data analysis. The study findings showed that this fatwa had a direct impact on reducing working hours, layoffs, and income instability for some Muslim workers. In addition, social and psychological pressures arose, including feelings of guilt, anxiety, and relational tensions in the work environment and surrounding community. Workers responded to this situation with various adaptation strategies: new workers tended to look for alternative jobs, while old workers chose to stay in order to maintain the economic stability of their families. This study concluded that this normative-recommendatory fatwa presented an ethical dilemma for Muslim workers between religious obedience and economic survival. Therefore, an inclusive and collaborative policy response was needed from the government, religious institutions, and society to assist affected workers in facing the socio-economic consequences of the fatwa.